The effect of play activities on motor ability of elementary school students - Almusyowir Ilyas; Ahmad Chaeroni; Gusril Gusril; Ilham Ilham (Journal of Educational and Learning Studies, 2026)
Motor development theory suggests that play-based activities promote motor competence by providing repeated, varied movement experiences that enhance coordination, balance, agility, and object-control skills through active exploration and practice. This study examines the effect of play-based activities on the motor ability of elementary school students. The study was motivated by the low level of motor skills among students at SDN 20/VI Muara Madras, reflected in their difficulty performing movement tasks during physical education classes and the reduced engagement in physical play due to increased gadget use and limited play facilities. A quantitative approach was employed using a quasi-experimental one-group pretest-posttest design. The sample consisted of 17 fifth-grade students selected through purposive sampling. Motor ability was assessed using the Scott Motor Ability Test, which comprises four components: Basketball Throw, 4-Second Dash, Wall Pass, and Standing Broad Jump. Data were analyzed using the Shapiro-Wilk normality test, the paired-sample t-test, and Cohen's d effect size. The mean motor ability score increased from 200.00 at pretest to 205.67 at posttest, representing a mean difference of 5.67 points. However, the paired-sample t-test indicated that this difference was not statistically significant (p = 0.096). The calculated Cohen's d of 0.429 indicated a moderate effect size. These findings indicate that the play-based intervention did not produce a statistically significant improvement in students' motor ability under the conditions of this study. Further research employing larger samples, longer intervention periods, and stronger experimental controls is recommended to clarify the effectiveness of play-based approaches in enhancing motor development among elementary school students.